Pengalaman Holistik Pasien Terhadap Loyalitas Pasien Melalui Kelekatan Pasien Rawat Inap di Rumah Sakit Mutiara Bunda Tulang Bawang - Riko Ribowo; Tina M. Barusman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The purpose of this study is to analyze the effect of holistic experience on patient attachment and patient loyalty among inpatients, as well as to examine the mediating role of patient attachment in the relationship between holistic experience and inpatient loyalty at Mutiara Bunda Tulang Bawang Hospital. The level of inpatient loyalty and the factors influencing it have not been empirically and systematically identified, particularly those related to holistic patient experience and patient attachment, as well as the mediating role of patient attachment. This study employs a quantitative approach using a survey method to examine the relationships among the variables. The research sample consists of 312 inpatients selected through purposive sampling, with data collected using Likert-scale questionnaires and analyzed using SEM-PLS. The results indicate that holistic experience has a positive and significant effect on patient attachment and also directly enhances patient loyalty. Patient attachment is found to have a positive and significant effect on patient loyalty and serves as a partial mediator in the relationship between holistic experience and patient loyalty. Furthermore, patient attachment demonstrates a more dominant influence on patient loyalty compared to holistic experience. Therefore, hospital management should integrate holistic patient experience, including physical comfort, emotional support, and quality interactions, into service policies and healthcare staff development to strengthen patient attachment and sustainably enhance patient loyalty.